2021
DOI: 10.1016/j.isci.2021.102898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time and titer in convalescent plasma therapy for COVID-19

Abstract: HighlightsThe benefit of convalescent plasma (CP) for patients with COVID-19 is still debated Only when provided at early disease stages, CP reduced COVID-19 mortality CP benefit on mortality does not increase when selecting high-antibody titers Early treatment with CP may maximize its clinical benefit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Several studies suggest that the effect of CCP is dependent on its antibody titers [ 10 , 18 ], hence the importance of proper donor selection. The concentration of antibodies is known to increase during the first week of symptoms [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that the effect of CCP is dependent on its antibody titers [ 10 , 18 ], hence the importance of proper donor selection. The concentration of antibodies is known to increase during the first week of symptoms [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the CONCOR-1 study, an international randomized controlled trial, aimed to assess the efficacy of this therapy using mortality and intubation of patients at day 30 as the primary endpoint [ 10 ]. The trial, and others as reviewed elsewhere [ 18 ], selected the CCP based on the titer of anti-SARS-CoV-2 antibodies to ultimately transfuse it to infected patients [ 10 ]. Ultimately, this study failed to show the superiority of CCP over standard of care and even raised the possibility of harmful effects in plasma with low antibody content [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 SRs included in the overview, 26 were focused exclusively on COVID-19 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], while three were focused on respiratory pandemics and on beta coronaviruses infections [ 10 , 19 , 30 ]. Two SRs [ 17 , 22 ] were a subgroup analysis of other reviews [ 16 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…74). The mortality of COVID-19 patients was significantly reduced when convalescent plasma was provided in the early stages of the disease, and the use of plasma with high antibody titers did not increase the risk of death compared with unselected plasma (Refs 75,76). The use of convalescent plasma not only transiently increased the level of systemic anti-SARS-CoV antibodies but also promoted the specific T-cell response (Ref.…”
Section: Antibody-based Therapiesmentioning
confidence: 99%